Changing Requirements in the Skills of Bankers: The Role of Work Tools and the Role of Learning - Kessler, Stefan [Verfasser] (My University, 2020)
"The dissemination of new digital technologies in the world of work has recently brought up many questions regarding the potentiality of fundamental shifts in the qualification structure across a variety of sectors and industries. While tasks might be executed by digital technologies, these new working technologies might put qualified work at stake and change the skills requirements in various occupations. This contribution seeks to discuss the interrelations between the digitalisation of work tools, the skills and changing work tasks of qualified workers within an increasingly information-based working environment. Work tools might be digital devices, software algorithms, and networked systems as well as the working technologies needed to produce these tools. New work tools require workers to adapt to new occupational prerequisites and thus entail learning processes. At the same time - through learning ? new work tools also offer opportunities to expand their professional expertise and to develop new practical skills. After examining the consequences of digitalisation for vocational skills and for learning, the interrelations between new work tools, skills, and learning are further illustrated in a case study from the Swiss banking sector, where tablet computers were introduced into initial vocational education and training (VET) as tools for vocational learning and as prospective new work tools (i.e. in the field of consultation)." (author's abstract; BIBB-Doku)
Keywords: S 6.4.1.2 Dienstleistungskaufleute; G 2.2.1 Technologisierung; I 2.2.1 Westeuropa; Bankkaufmann; Berufsausbildung; Qualifikationswandel; Digitalisierung; Arbeitsmittel; Schweiz